2016
DOI: 10.1111/gbi.12173
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Fe(III) oxide reduction potential in Chocolate Pots hot spring, Yellowstone National Park

Abstract: Chocolate Pots hot springs (CP) is a unique, circumneutral pH, iron-rich, geothermal feature in Yellowstone National Park. Prior research at CP has focused on photosynthetically driven Fe(II) oxidation as a model for mineralization of microbial mats and deposition of Archean banded iron formations. However, geochemical and stable Fe isotopic data have suggested that dissimilatory microbial iron reduction (DIR) may be active within CP deposits. In this study, the potential for microbial reduction of native CP F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 114 publications
(218 reference statements)
7
57
1
Order By: Relevance
“…This is in contrast to other iron-rich, neutral pH systems including hot and cold springs and groundwater seeps (e.g., Blöthe & Roden, 2009;Fortney et al, 2016;Hegler et al, 2012;Roden et al, 2012). This may partially reflect the relative fluxes of iron oxidation versus organic carbon fixation at OHK; that is, there is insufficient organic carbon being fixed in this environment to fuel substantial iron oxide respiration.…”
Section: Low Biomass Yield Of the Ohk Microbial Communitymentioning
confidence: 85%
See 1 more Smart Citation
“…This is in contrast to other iron-rich, neutral pH systems including hot and cold springs and groundwater seeps (e.g., Blöthe & Roden, 2009;Fortney et al, 2016;Hegler et al, 2012;Roden et al, 2012). This may partially reflect the relative fluxes of iron oxidation versus organic carbon fixation at OHK; that is, there is insufficient organic carbon being fixed in this environment to fuel substantial iron oxide respiration.…”
Section: Low Biomass Yield Of the Ohk Microbial Communitymentioning
confidence: 85%
“…The majority of Chlorobi sequences found in OHK appear to fall within the Chlorobi order Ignavibacteria, a basal clade of Chlorobi whose known members include versatile heterotrophic metabolisms but no known phototrophy pathways (Iino et al, 2010;Liu, Frigaard et al, 2012). Ignavibacteria appear to be a common component of hot spring microbial communities: these organisms were first isolated from a Japanese hot spring (Iino et al, 2010) and are found at high abundance in Chocolate Pots hot springs in Yellowstone National Park (Fortney et al, 2016). Ignavibacteria appear to be a common component of hot spring microbial communities: these organisms were first isolated from a Japanese hot spring (Iino et al, 2010) and are found at high abundance in Chocolate Pots hot springs in Yellowstone National Park (Fortney et al, 2016).…”
Section: Anoxygenic Phototrophs and Relativesmentioning
confidence: 99%
“…Experiments with HM and/or glucose had PCC genes mainly assigned to Geobacter and Geothrix, whereas HA reactors had increases in Ignavibacterium/Melioribacter related taxa. The latter taxa are known to be capable of fermentative growth with polysaccharides as well as DIR; 22,23,59 thus the presence of both PCC and CAZyme genes (see Figure 3) attributable to these organisms in the HA cultures suggests that they played a role both in DIR and upstream production of fermentation end-products that served as substrates for DIR. It is notable that our findings reveal for the first time that the previously described DIRB Geothrix 60 contains PCC gene systems for reduction of extracellular electron acceptors (see SI Figure S1 and Supporting Text 1).…”
Section: Resultsmentioning
confidence: 99%
“…The relatively high concentrations of dissolved organic carbon (DOC) measured in Pool 1 (∼1.3 mM) may stimulate heterotrophic activity by the microbial community at Jinata, coupled to aerobic or anaerobic respiration (such as dissimilatory iron reduction, as observed in other iron-rich hot springs, e.g. 33), resulting in the drawdown of DOC downstream. The source of this DOC is unclear; future work will be necessary to determine whether DOC is present in the source water or if it is produced in situ by the microbial community in the Source Pool and Pool 1.…”
Section: Discussionmentioning
confidence: 99%